2022
DOI: 10.1177/10762175221131055
|View full text |Cite
|
Sign up to set email alerts
|

Using Behavioral Engagement Measures of Multiple Learning Profiles to Recognize Twice-Exceptional Students

Abstract: Using the ECLS-K:2011, a nationally representative dataset, we compared measures of behavioral engagement among students with four different learning profiles: students identified with learning disabilities, students identified as gifted, students identified as both gifted and having a learning disability (twice-exceptional; 2e), and general education students. Behavioral engagement focuses on conduct in class, participation in school-related activities, and interest in academic tasks. We detected differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Interestingly, they also report that in all cases included in their study, it was the parents who were the initiators in the process of identification [6]. Another study [14] found that among surveyed parents of gifted children, 72% of the parents of gifted-only students had suspected giftedness before the age of school entrance, while the number among parents with 2e students was as high as 90%.…”
Section: Parentsmentioning
confidence: 91%
See 4 more Smart Citations
“…Interestingly, they also report that in all cases included in their study, it was the parents who were the initiators in the process of identification [6]. Another study [14] found that among surveyed parents of gifted children, 72% of the parents of gifted-only students had suspected giftedness before the age of school entrance, while the number among parents with 2e students was as high as 90%.…”
Section: Parentsmentioning
confidence: 91%
“…Several very recent articles also include educational needs or requirements in their definitions of twice exceptionality or of 2e students. For example, Hulsey et al [14] (p. 16) describe twice exceptionality as a "blend of gifted and special education characteristics ("exceptionalities") that require a flexible educational approach". In a similar vein, Lien et al [15] (p. 2) define 2e students as "those who have coexisting giftedness and disabilities in one or more domains that need support from both gifted and disability education".…”
Section: Definitions Characteristics and Identificationmentioning
confidence: 99%
See 3 more Smart Citations